Media Sosial Instagram Sebagai Sarana dalam Menciptakan Brand Image Bagi Klub Indonesia Muda - Hariawati, Tresiana; Loisa, Riris (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
The development of sports in Indonesia is growing rapidly, one of which is basketball. Currently there are many basketball clubs, one of which is the Indonesia Muda club which has been around for a long time. Every club should want to be known by the public to increase their popularity. To increase the popularity of young Indonesian basketball clubs, a brand image is needed as a reflection of society towards the club. The way for young Indonesian clubs to increase brand image by using social media in the form of Instagram. The problem raised is how sports clubs do brand image on Instagram social media to attract followers. Aims to find out how the basketball club does brand image on social media to attract public attention, especially on social media Instagram to get followers. The theory used is in the form of communication, brand image, and Instagram social media. This research method is a qualitative case study with interviews, observation, and documentation. Data processing and analysis techniques used Coding (open coding, axial coding, and selective coding) for validity using triangulation. The results of the study can be concluded that the way young Indonesian clubs do brand image by posting training schedules for age groups, documentation during training, achievements per age group when participating in matches, responding to an incident, also interacting with followers through stories containing QnA (question and answer). What the Indonesia Muda club is doing can attract people to follow the IM club's Instagram. Coupled with the statement by the IM club Instagram holder who said that every month there is an increase in followers. Perkembangan olahraga di Indonesia semakin berkembang pesat salah satunya adalah cabang olahraga basket. Saat ini sudah banyak klub basket yang ada, salah satunya klub Indonesia Muda yang sudah berdiri sejak lama. Setiap klub seharusnya ingin dikenal oleh masyarakat agar meningkatkan popularitas. Untuk meningkatkan popularitas klub basket Indonesia muda dibutuhkan brand image (citra merek) sebagai gambaran masyarakat terhadap klub. Cara klub Indonesia muda untuk meningkatkan brand image dengan menggunakan media sosial berupa instagram. Masalah yang diangkat adalah bagaimana klub olahraga melakukan brand image di media sosial instagram untuk menarik followers. Tujuan penelitian ini untuk mengetahui cara klub basket melakukan brand image di media social untuk menarik perhatian masyarakat khususnya di media social Instagram agar memperoleh followers. Teori yang dipakai berupa komunikasi, citra merek (brand image), dan media sosial Instagram. Metode penelitian ini adalah kualitatif studi kasus dengan wawancara, observasi, dan dokumentasi. Hasil penelitian dapat disimpulkan, klub Indonesia muda melakukan branding di media sosial dengan memposting jadwal latihan kelompok umur, dokumentasi saat latihan berlangsung, prestasi per kelompok umur saat mengikuti pertandingan, merespon suatu kejadian juga berinteraksi dengan followers melalui story yang berisi QnA (tanya jawab).